MANAJEMEN REFERENSI TERKAIT EKOSISTEM MANGROVE BERBASIS GOOGLE DRIVE UNTUK MENDUKUNG KEMUDAHAN AKSES REFERENSI DIGITAL: Management Related To The Mangrove Ecosystem Based On Google Drive To Support Easy Access To Digital Reference - Rahman Rahman; Martha L. Wattimena; Frijona F. Lokollo; Krisye Krisye; Sophia N.M. Fendjalang; Nur Tasmiah Sirajuddin (Pakis Journal Institute, 2023)
Google Drive-based reference management has just existed for easy access to referrals in mangrove ecosystem studies. Google Drive is a popular and widely used file storage and sharing platform. We can store, organize, and share various documents and files using Google Drive, including reference documents, scientific journals, and other essential mangrove resources. Cloud-based Google Drive allows easy access and efficient collaboration between individuals or groups in managing or researching mangroves. This service activity aims to create a mangrove reference database based on several topics using Google Drive so that mangrove observers can easily access it. Reference searches were carried out on the websites googlescholar.com and sciencedirect.com. The activity obtained 580 references from national and international scientific articles and mangrove e-books. The sorting results folder includes mangrove e-books, mangrove ecotourism, mangrove carbon emissions, mangrove litter production, mangrove carbon stocks, and mangrove economic valuations. Articles in the reference folder can be accessed via the link. https://drive.google.com/drive/folders/1km7IZDFURwnEabFOXnVG0e4SZRHxvWdn?usp=drive_link.